Comparative Analysis of the Concepts of Translation, Tafsir, and Ta’wil According to Abdul Azim Al-Zarqani and Manna’ Khalil Al-Qattan: A Comparative Study of the Views of Abdul Azim Al-Zarqani and Manna’ Khalil Al-Qattan - Azhar, Ruly Syaepul; Sanah , Siti (Pondok Pesantren Hamalatul Qur'an Jogoroto Jombang, 2025)
The Qur'an, as a guide for the lives of Muslims, must be implemented in daily life. However, because the Qur'an was revealed in Arabic—a language not understood by everyone—Muslims are required to study the sciences that aim to comprehend the meaning of the Qur'an, namely translation (terjemah), exegesis (tafsir), and interpretation (ta'wil). Due to the various opinions on these subjects, it is essential to focus on the perspectives of one or two scholars. The purpose of this research is to understand the concepts of translation, exegesis, and interpretation according to Abdul Azim Al-Zarqani and Manna' Khalil Al-Qattan, and then compare their views to identify similarities and differences. The research method used is qualitative with a comparative study approach. Data collection was conducted using documentation techniques. The data analysis techniques included data collection, data reduction, data presentation, as well as verification and conclusion. The results of the study show three similarities and four differences in the concept of translation, as well as two similarities and one difference in the concepts of exegesis and interpretation, as understood by Abdul Azim Al-Zarqani and Manna' Khalil Al-Qattan.